The Short-Term Effect of Slope Walking on Soleus H-Reflexes in People with Multiple Sclerosis. (1st November 2018) - Hoque, Maruf M.; Sabatier, Manning J.; Borich, Michael; Kesar, Trisha; Backus, Deborah
Highlights: People with Multiple Sclerosis (PwMS) can walk downslope (−7.5%) continuously for 20 min. DSW is a feasible intervention for PwMS with no observed adverse events and no greater exertion than LW. DSW induces greater short-term H-reflex depression than level walking or upslope walking. Abstract: Downslope walking (DSW) causes H-reflex depression in healthy adults, and thus may hold promise for inducing spinal reflex plasticity in people with Multiple Sclerosis (PwMS). The study purpose was to test the hypothesis that DSW will cause acute depression of spinal excitability in PwMS. Soleus H-reflexes were measured in PwMS ( n = 18) before and after 20 min of treadmill walking during three visits. Participants walked on a different slope each visit [level: 0% level walking (LW), upslope: +7.5% treadmill walking with an upslope (USW) or downslope: −7.5% (DSW)]. The soleus H max / M max ratio was used to measure spinal excitability. Heart rate and ratings of perceived exertion (RPE) were measured during walking. DSW induced the largest change in spinal excitability (a 26.7% reduction in soleus H max / M max ( p = 0.001)), although LW also reduced H max / M max (-5.3%, p = 0.05). Heart rate ( p < 0.001) was lowest for DSW, and RPE for DSW did not exceed "Fairly light". DSW evokes short-term spinal plasticity in PwMS, while requiring no greater effort than LW. Our results suggest that PwMS retain the capacity for DSW-induced short-term spinal reflex modulation previously found in healthy adults. These results may provide a foundation for further investigation of long-term effects of DSW on spinal reflex plasticity and functional ability in PwMS.